Migrace a etnokulturní procesy jako součást každodennosti bulharského venkova - Barbora Machová (AntropoWebzin, 2010)
This paper deals with terms of everyday life or everyday culture. It focuses on migration and ethnocultural processes in south Bulgaria, as they are part of everyday life of people in the region. In a field research I made in south Bulgaria in 2008 I focused on two particular elements of villagers’ everyday life during 20th and 21 century. First, migration and its consequences, ethnocultural processes, second, changes in the everyday rhythm of work in local communities. Migration was widely extensive on the Balkans during the Ottoman period, the whole 20th century, as well as at the beginning of the 21th century. It is a “universal” social phenomenon which happens in certain regions within various circumstances, as it is influenced by a different political or economical situation. The term of everyday life can be specified from different points of view: as everydayness (in contrast to festivity), regularly repeated activity, „small“ history in contrast to „big“ historic events, or private life in contrast to social life. During the second half of the 20th century, „traditional“ categories in European ethnology, such as material, social and spiritual culture, were replaced by a new broad concept of everyday culture. By doing so, ethnology approached the holistic concept of anthropology. Despite the fact, ethnology classifies culture into categories such as occupation, household, family or personal values. Thus, the major change in the ethnological approach is that it pays more attention to everydayness nowadays. Therefore, it is not an easy task to investigate everydayness. For the purpose, ethnology usually uses the method of field research, participant observation is suitable to investigate immediate everydayness, structured and semi-structured interviews were used to study everyday culture in the 70s.